1992
DOI: 10.21273/hortsci.27.7.809
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Storage Time Affect Quality of Yellow Passion Fruit

Abstract: Vine-ripened yellow passion fruit (Passiflora edulis f. flavicarpa Deg.) packed and shipped from Homestead, Fla., were stored for 15, 30, or 45 days at 5, 10, or 15C. Fruit analyzed immediately on arrival had the best external appearance and highest fruit weight. Fruit weight loss increased with storage time at all temperatures and the response was linear. Fruit external appearance deteriorated rapidly at 5 and 15C. Pulp percentage at 5C increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 2 publications
2
9
0
3
Order By: Relevance
“…fruits have been carried out, where the temperature varied between 6.5 °C and 12 °C and relative humidity between 85 and 90% (Arjona et al, 1992;Silva et al, 1999;Zapata, 1987;Rinaldi et al, 2017b). Arjona et al (1992), reported a 30-day shelf life for yellow passion fruit (Passiflora edulis) stored at 10 °C and 85% relative humidity. For Passiflora alata fruits, the temperature of 10 °C and 90% relative humidity were recommended during storage (Rinaldi et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…fruits have been carried out, where the temperature varied between 6.5 °C and 12 °C and relative humidity between 85 and 90% (Arjona et al, 1992;Silva et al, 1999;Zapata, 1987;Rinaldi et al, 2017b). Arjona et al (1992), reported a 30-day shelf life for yellow passion fruit (Passiflora edulis) stored at 10 °C and 85% relative humidity. For Passiflora alata fruits, the temperature of 10 °C and 90% relative humidity were recommended during storage (Rinaldi et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…A colheita do maracujá é feita com os frutos caídos ao solo ou presos nas ramagens da planta, num estádio de maturação em que a casca se encontra com coloração predominantemente amarela. Neste estádio, o fruto é bastante sensível à perda de água, ao murchamento, facilitando a contaminação por microrganismos e contribuindo para diminuir seu período de conservação pós-colheita (Arjona et al, 1992;Durigan, 1998;Marchi et al, 2000).…”
Section: Introductionunclassified
“…Fruit were analyzed after 15 and 30 days of storage for the following characteristics: 1) external appearance (percentage of surface shriveled), 2) weight, 3) pulp percentage (weight of fleshy pericarp and seeds divided by fruit weight × 100), 4) juice pH, 5) total soluble solids concentration (SSC), and 6) juice fructose, glucose, and sucrose contents determined by high-performance liquid chromatography following the method of Arjona et al (1992). Fruit weight loss was calculated by subtracting fruit weight at the end of the storage period from the initial weight.…”
Section: Methodsmentioning
confidence: 99%
“…Passion fruit stored at 5C and 85% relative humidity (RH) lost moisture rapidly; 80% of the fruit surface was shriveled after 3 days in storage (Arjona et al, 1992). While passion fruit juice remained wholesome for 7 days, fruit began shriveling soon after abscission (Knight and Sauls, 1983).…”
mentioning
confidence: 99%